OPTIMALISASI PEMANFAATAN LAHAN TANAMAN OBAT KELUARGA DI WILAYAH KERJA PUSKESMAS KOTA PANGKAJENE, KABUPATEN PANGKEP - Nur Wahyuni Munir; Sunarti (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2021)
Family Medicinal Plants (abbreviated TOGA) are home-grown plants that have medicinal properties. The family medicine garden land is essentially a plot of land, both in the yard, garden or field that is used to cultivate medicinal plants as medicine in order to meet the family's needs for medicines. Partner problems found include lack of family knowledge and public awareness about the use of TOGA and optimizing the use of family medicinal plant land, lack of TOGA books as a reference in making TOGA ingredients and lack of clues about names and the benefits of each TOGA. Implementation of services that have been carried out in the form of providing counselin about TOGA, provision and planting of TOGA seedlings, making plant labels and procurement of TOGA books both in the pilot area of the Pangkajene Community Health Center in Pangkep district as well as in a number of pilot areas of residents and their respective residents lands. In conclusion, increased knowledge and skills of families in utilizing family medicinal plants, availability of 100 TOGA seeds for residents and health centre, the creation of a pilot TOGA land at the Pangkajene City Health Centre and the availability of TOGA books at the Pangkajene City Health Centre. Recommendations the need for periodic monitoring of the sustainability of the pilot TOGA at the Pangkajene City Health Centre and those distributed to residents and the pilot TOGA should be added to other plants besides the seeds distributed by the service team. Keywords: Optimization, Land Use, Family Medicinal Plants